Effects of FDI spillover on regional productivity: Evidence from panel data analysis using stochastic frontier analysis - Ramasamy, M. (Emerald Group Publishing Ltd., 2017)
Purpose: When spillovers are measured at a national level, the regional benefits may not be identified if they are too small. Very few studies that examined how FDI impacts the regional productivity of the host nations have shown mixed results. The evidence is still scarce and little is known about how the regional penetration of FDI affects the regional productivity performance. The trajectory of regional productivity growth in India has been a subject of scrutiny and intense debates and remains less systematically investigated. The purpose of this paper is to fill this lacuna by investigating the effect of FDI spillover on regional productivity in Indian states. Design/methodology/approach: Using data supplied by the Central Statistical Organization, National Statistical Organization, National Sample Survey Office, and National Accounts Statistics, Government of India at the Indian Ministry of Statistics and Programme Implementation, first, the study employs stochastic frontier model to explore the extent to which FDI spillover contributes to the regional productivity from panel data of 28 Indian states over 1993-2013. Second, the study examines the roles of absorptive ability and technology gap on productivity effect of FDI. Third, by adopting SFA, we measure productivity growth of Indian states in terms of Malmquist productivity index. Fourth, India’s development is imbalanced. To analyze the imbalance due to skewed distribution of FDI among Indian states, Indian states are divided into three regions, and the spillover effects of FDI on TFP in these regions are explored. Findings: The results on the effects of FDI spillover on regional productivity in India using stochastic frontier and panel data from 28 states over 1993-2013 show that R&D, technology import, human capital, and various specifications of FDI have a significant impact on the regional productivity in India except technology gap. Study does not find support for the resource curse hypothesis in Indian states. Productivity growth for India using the Malmquist TFP index based on the stochastic frontier shows positive impact. The TFP growth in the three regions of India is turned to be differently attributed by the FDI spillover. Originality/value: Little is known about how the regional penetration of FDI affects the regional productivity performance. This research aims to fill this lacuna by investigating the effect of FDI spillover on regional productivity in Indian states which has been a subject of scrutiny and intense debates. © 2017, © Emerald Publishing Limited.